2013
DOI: 10.2136/vzj2012.0086
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the Location of Preferential Flow Paths of a Leachate Plume by Using a DUALEM‐421 and a Quasi‐Three‐Dimensional Inversion Model

Abstract: In urban landscapes, information is required to describe the heterogeneous nature of pedological and hydrological resources. This is particularly the case in areas previously used as municipal landfills. Increasingly, geophysical techniques such as electromagnetic (EM) induction are being used. Here we describe how a single‐frequency and multiple‐coil EM instrument can be used in conjunction with a one‐dimensional spatially constrained quasi‐three‐dimensional inversion algorithm to map electrical conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…One possible option is the use of gamma‐ray (γ‐ray) spectrometry data, as various authors have shown that γ‐ray data is suitable for developing MLR models to predict topsoil clay at the field scale (Pracilio et al ., ) and sand content at the district level (Spadoni & Voltaggio, ). Moreover, although we have used the raw EC a of the EM38 and EM31, it might be possible to achieve better results by trying to establish MLR relationships using estimates of the true electrical conductivity (σ – mS/m) by using EM inversion software (Triantafilis & Monteiro Santos, and Triantafilis et al ., ,b).…”
Section: Resultsmentioning
confidence: 99%
“…One possible option is the use of gamma‐ray (γ‐ray) spectrometry data, as various authors have shown that γ‐ray data is suitable for developing MLR models to predict topsoil clay at the field scale (Pracilio et al ., ) and sand content at the district level (Spadoni & Voltaggio, ). Moreover, although we have used the raw EC a of the EM38 and EM31, it might be possible to achieve better results by trying to establish MLR relationships using estimates of the true electrical conductivity (σ – mS/m) by using EM inversion software (Triantafilis & Monteiro Santos, and Triantafilis et al ., ,b).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the collection of σ a data could be undertaken on 5‐m transects as opposed to the 25 m used here. In the latter case, a 1‐D spatially constrained quasi‐3‐D inversion algorithm could be employed (Triantafilis et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…First, quasi‐2D inversions were conducted using the EC a data collected on each day at the 22 measurement locations. To determine the best EMCI with respect to θ , EM4Soil was run with different parameters (Triantafilis & Monteiro Santos, ; Triantafilis et al ., ,b; Huang et al ., ). This included forward modelling, either based on the cumulative function (CF) (McNeill, ) or the full solution (FS) of electromagnetic fields in a layered earth (Keller & Frischknecht, ), inversion algorithms (i.e.…”
Section: Methodsmentioning
confidence: 99%